Where the Spirits Ride the Wind : Trance Journeys and Other Ecstatic Experiences - Goodman, Felicitas D. (Book collections on Project MUSE., 1990)
""The book is clearly written for the general reader and includes many descriptions of trance experiences. It may serve as a good introduction to the nature and appeal of the shamanic revival in modern Western cultures.""--Theological Book Review"" ... a case study in experiential anthropology that offers a unique mix of autobiography, mythology, experiential research, and archaeological data to support a challenging thesis-that certain body postures may help induce specific trance states."" -Shaman's Drum""This is a spellbinding and exceptionally readable book by an extraordin